PENGAJARAN MUSIK GEREJA BERCIRIKAN PENTAKOSTA KARISMATIK: SEBUAH KAJIAN BAGI PENDIDIKAN MUSIK GEREJA MASA KINI - sema, daniel (Shift Key : Jurnal Teologi dan Pelayanan, 2019)
Music in the charismatic Pentecostal church service plays a very important role for it is believed to be the most suitable means to express great joy in celebrating the victory of Jesus Christ from death. This worship model is believed to enable the Holy Spirit to work as widely as possible for the congregation, so that the events of ecstasy, glossolalia, testimony about having a vision are not considered strange any more.Due to the celebratory nature of worship, suitable songs and music are chosen. The songs are contemporary and not hymn-shaped; the musical accompaniment format is a complete band that is supported by sophisticated sound system, the worship procedure is simple and is led by a worship leader (WL). However, to build a musical arrangement which is able to support congregants to sing in a charismatic pentecostal worship is not easy because musicians are required to be able to appreciate songs, have adequate skills, and good musical knowledge.The purpose of this study is to obtain an appropriate method in teaching charismatic pentecostal music to novice musicians.